Simultaneous estimation of the nutritional contribution of fish meal, soy protein isolate and corn gluten to the growth of Pacific white shrimp (Litopenaeus vannamei) using dual stable isotope analysis - Gamboa Delgado, Julián; Casas Rojas, Monica Guadalupe; Nieto López, Martha Guadalupe; Cruz Suárez, Lucía Elizabeth (Blackwell Science Pub., 2012)
The nutritional contribution of the dietary nitrogen, carbon and total dry matter supplied by fish meal (FM), soy protein isolate (SP) and corn gluten (CG) to the growth of Pacific white shrimp Litopenaeus vannamei was assessed by means of isotopic analyses. As SP and CG are ingredients derived from plants having different photosynthetic pathways which imprint specific carbon isotope values to plant tissues, their isotopic values were contrasting. FM is isotopically different to these plant meals with regards to both, carbon and nitrogen. Such natural isotopic differences were used to design experimental diets having contrasting isotopic signatures. Seven isoproteic (36% crude protein), isoenergetic (4.7 kcal g−1) diets were formulated; three diets consisted in isotopic controls manufactured with only one main ingredient supplying dietary nitrogen and carbon: 100% FM (diet 100F), 100% SP (diet 100S) and 100% CG (diet 100G). Four more diets were formulated with varying mixtures of these three ingredients, one included 33% of each ingredient on a dietary nitrogen basis (diet 33FSG) and the other three included a proportion 50:25:25 for each of the three ingredients (diets 50FSG, 50SGF and 50GFS). At the end of the bioassay there were no significant differences in growth rate in shrimps fed on the four mixed diets and diet 100F (k=0.215–0.224). Growth rates were significantly lower (k=0.163–0.201) in shrimps grown on diets containing only plant meals. Carbon and nitrogen stable isotope values (δ13C and δ15N) were measured in experimental diets and shrimp muscle tissue and results were incorporated into a three-source, two-isotope mixing model. The relative contributions of dietary nitrogen, carbon and total dry matter from FM, SP and CG to growth were statistically similar to the proportions established in most of the diets after correcting for the apparent digestibility coefficients of the ingredients. Dietary nitrogen available in diet 33FSG was incorporated in muscle tissue at proportions representing 24, 35 and 41% of the respective ingredients. Diet 50GSF contributed significantly higher amounts of dietary nitrogen from CG than from FM. When the level of dietary nitrogen derived from FM was increased in diet 50FSG, nutrient contributions were more comparable to the available dietary proportions as there was an incorporation of 44, 29 and 27% from FM, SP and CG, respectively. Nutritional contributions from SP were very consistent to the dietary proportions established in the experimental diets.